Analisis SWOT Manajemen Berbasis Sekolah dalam Upaya Penyelenggaraan Sekolah Efektif di SMP Negeri Se-Kecamatan Darul Imarah Kabupaten Aceh Besar - Fitriah, Fitriah; Musdiani, Musdiani; Rahmattullah, Rahmattullah (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to describe the implementation of based management and analyze the strengths, weaknesses, opportunities, and threats of the principal's strategy towards the implementation of school-based management. This type of research uses descriptive qualitative. Data were collected through observation and interviews. The data analysis technique used is qualitative data analysis with stages, namely data reduction, data presentation, and conclusion drawing. The research results show that the SWOT analysis can be understood; Strength at State Junior High School 1 Darul Imarah, each member of the school has their own advantages, as the main capital for the school. Meanwhile, Darul Imarah State Junior High School 2 can collaborate, build communication, and share with each other. Weaknesses at State Junior High School 1 Darul principal in implementing School Based Management are still not optimal, because there are still many things that need to be considered, various learning media have not been fulfilled because there are still many other needs that must be prioritized. Opportunities for State Junior High School 1 Darul Imarah are the level of success in producing a quality generation and being able to compete to enter well-known schools. State Junior High School 2 Darul Imarah provided a positive response from every school member, information, and outreach regarding educational programs. Threats of Darul Imarah State Junior High School 1 still have many programs that have not been achieved. Meanwhile, at State Junior High School 2 Darul Imarah there are still several school members who raise pros and cons regarding the rules that have been set